190k views
3 votes
Evaluate the limit, if it exists.
lim (h - > 0) ((-7 + h)^2 - 49) / h

User Peduarte
by
5.4k points

1 Answer

4 votes

Expand everything in the limit:


\displaystyle\lim_(h\to0)\frac{(-7+h)^2-49}h=\lim_(h\to0)\frac{(49-14h+h^2)-49}h=\lim_(h\to0)\frac{h^2-14h}h

We have
h approaching 0, and in particular
h\\eq0, so we can cancel a factor in the numerator and denominator:


\displaystyle\lim_(h\to0)\frac{h^2-14h}h=\lim_(h\to0)(h-14)=\boxed{-14}

Alternatively, if you already know about derivatives, consider the function
f(x)=x^2, whose derivative is
f'(x)=2x.

Using the limit definition, we have


f'(x)=\displaystyle\lim_(h\to0)\frac{f(x+h)-f(x)}h=\lim_(h\to0)\frac{(x+h)^2-x^2}h

which is exactly the original limit with
x=-7. The derivative is
2x, so the value of the limit is, again, -14.

User Kacey Ezerioha
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.